Predicting effective teaching skills based on faculty members' orientations toward their academic specializations at the College of Physical Education and Sports Sciences at Koya University - Amin, Prof. Dr. Rebaz Majeed Amin (Sulaimani Journal for Humanities, 2025)
The research aims to predict effective teaching skills in terms of faculty members’ attitudes toward their academic specializations in the College of Physical Education and Sports Sciences at Koya University. The research sample consisted of (50) faculty members in the College of Physical Education and Sports Sciences at Koya University. The two research tools consisted of a measure of effective teaching skills and a measure of attitudes toward their specializations for the academic subject they teach. The researcher took care to provide honesty. And the reliability of the research tools. After applying the two standards to the research sample, collecting the data and processing it with appropriate statistical means, a set of conclusions were reached, the most important of which are: Ø There is great interest by faculty members about the importance of the areas of teaching skills (knowledge of the specialized subject - preparing and organizing the curriculum - preparing lessons - teaching the subject - measurement and evaluation). Ø The areas of teaching skills (preparing and organizing the curriculum - preparing lessons - measuring and evaluating) contribute greatly to influencing the attitudes of faculty members towards their scientific specializations. The researcher recommended the necessity of relying on the teaching skills that were achieved in the process of preparing and training faculty members in the College of Physical Education and Sports Sciences at Koya University.
Keywords: effective teaching skills; orientation towards academic specialization